Characterization and Antibiofouling Performance Investigation of Hydrophobic Silver Nanocomposite Membranes: A Comparative Study - Maryam Amouamouha; Gagik Badalians Gholikandi (Membranes, 2017)
Biofouling is one of the drawbacks restricting the industrial applications of membranes. In this study, different thicknesses of silver nanoparticles with proper adhesion were deposited on poly(vinylidenefluoride) (PVDF) and polyethersulfone (PES) surfaces by physical vapor deposition (PVD). The crystalline and structural properties of modified and pure membranes were investigated by carrying out X-ray diffraction (XRD) and attenuated total reflectance Fourier transform infrared spectroscopy (ATR-FTIR). Scanning electron microscope (SEM) and atomic force microscopy (AFM) analyses were employed to examine the surface morphology and the bacteria anti-adhesion property of the membranes. The morphology measurements confirmed that even though after silver grafting the surface became more hydrophobic, the homogeneity increased and the flux reduction decreased after coating. Moreover a comparison between PVDF and PES revealed that CFU (colony forming units) reduced 64.5% on PVDF surface and 31.1% on PES surface after modification. In conclusion, PVD improved the performance of the membrane antibiofouling, and it is more promising to be used for PVDF rather than PES.